Peningkatan Belajar Siswa Ditinjau Dari Pendampingan Orang Tua Dan Lingkungan Belajar - Hapsari Dwi Yulia; Suyitno; Sripit Widiastuti (Program Studi PGSD Universitas Madako Tolitoli, 2024)
Learning motivation is a crucial element in improving students' academic achievement. Approaches that involve parental mentoring variables and the learning environment are important steps in understanding and increasing student motivation. This study adopts a quantitative approach with a focus on grade IV students as the study population. A total of 69 students were sampled. The results showed that parental assistance and the learning environment had a significant impact on student learning motivation. It was found that parental assistance had an influence of 69.9%, while the learning environment influenced learning motivation by 37.8%. This finding highlights the importance of these independent factors in increasing the enthusiasm for learning of students at the elementary school level, especially in grade IV Cluster 3 of Srengat District, Blitar Regency. This study contributes to the study of the analysis of learning motivation of elementary school students with the following findings. Parental assistance (X1) and learning environment (X2) have a significant effect on student learning motivation. Parental support increases learning motivation, while a supportive learning environment also increases students' desire to learn. The implications of research can inspire parents to intensify their guidance in motivating children's learning.